2020
DOI: 10.1080/09553002.2020.1812759
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of posterior subcapsular cataracts based on a review of risk factors including aging, diabetes, and ionizing radiation

Abstract: Purpose: Since the exact development of posterior subcapsular cataracts (PSCs) is poorly understood, we review various risk factors and propose a two-stage etiology for PSCs. Methods: The biological mechanisms associated with age-related cataracts (primarily nuclear cataracts, cortical cataracts and PSCs) were reviewed in relation to selected risk factors that induce PSCs (including atopy, diabetes, hypoparathyroidism, myopia, retinitis, solar radiation, steroid use, uveitis, vitrectomy and ionizing radiation)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 200 publications
(284 reference statements)
0
35
0
1
Order By: Relevance
“…For example, oxidative stress, especially GSH depletion, is regarded as the hallmark of ARNC [ 16 ]. Ionic imbalance caused by loss of Na + /K + -ATPase function and water content increase is the proposed mechanism for cortical cataract genesis, while ARPSC is more common in patients with retinitis pigmentosa, diabetes, myopia, and long-term use of corticosteroids [ 49 , 50 ]. Thus, it is no surprise that the relative mRNA expressions of Nrf2, HO-1, and BVRA, which are crucial for resisting oxidative stress, were all decreased in the LECs of ARNC patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, oxidative stress, especially GSH depletion, is regarded as the hallmark of ARNC [ 16 ]. Ionic imbalance caused by loss of Na + /K + -ATPase function and water content increase is the proposed mechanism for cortical cataract genesis, while ARPSC is more common in patients with retinitis pigmentosa, diabetes, myopia, and long-term use of corticosteroids [ 49 , 50 ]. Thus, it is no surprise that the relative mRNA expressions of Nrf2, HO-1, and BVRA, which are crucial for resisting oxidative stress, were all decreased in the LECs of ARNC patients.…”
Section: Discussionmentioning
confidence: 99%
“…When untreated, uveitis can lead to scarring, swelling or detachment of the retina, optic nerve damage, glaucoma, and lens cataract, all of which are associated with vision loss. While this inflammatory disease has been linked to cataract formation [202], the exact mechanism is not yet known. In contrast, there is a significant literature showing post-cataract surgery complications in patients with uveitis, particularly if inflammation is not controlled prior to surgery.…”
Section: The Impact Of Uveitis On Cataract Surgery Outcomesmentioning
confidence: 99%
“…Despite advances in surgical techniques, PPV frequently results in cataract, with some studies suggesting the rate of progression to visually significant nuclear sclerotic cataract is as high as 100% (Cheng et al 2001;Do et al 2018). Several hypotheses for this have been proposed including injury to the crystalline lens at the time of PPV, phototoxicity and lens protein oxidation (Hsuan et al 2001;Soliman et al 2018;Richardson et al 2020). Prior studies have suggested that while cataract surgery may improve visual acuity after PPV, it is associated with higher rates of intraoperative complications, including zonulopathy (such as zonular dehiscence or the need for a capsular tension ring), prolapsed lens fragments and posterior capsular tears (Grusha et al 1998;Pinter & Sugar 1999;Soliman et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…2018; Richardson et al. 2020). Prior studies have suggested that while cataract surgery may improve visual acuity after PPV, it is associated with higher rates of intraoperative complications, including zonulopathy (such as zonular dehiscence or the need for a capsular tension ring), prolapsed lens fragments and posterior capsular tears (Grusha et al.…”
Section: Introductionmentioning
confidence: 99%